Middle class construction: domestic architecture, aesthetics and anxieties in Tanzania. Issue 2 (30th April 2014) - Mercer, Claire
ABSTRACT This paper examines the new styles of houses under construction in contemporary Tanzania and suggests that they can be understood as the material manifestation of middle class growth. Through an examination of the architecture, interior decor and compound space in a sample of these new houses in urban Dar es Salaam and rural Kilimanjaro, the paper identifies four domestic aesthetics: the respectable house, the locally aspirant house, the globally aspirant house and the minimalist house, each of which map on to ideas about ujamaa, liberalisation and the consumption of global consumer goods in distinct ways. The paper argues that these different domestic aesthetics demonstrate intra-class differences, and in particular the emergence of a new middle class.